Pay satisfaction and work–family conflict across time. (2nd October 2012) - Bhave, Devasheesh P.; Kramer, Amit; Glomb, Theresa M.
Summary On the basis of justice and exchange theories, the authors propose that employees offset their levels of work–family conflict (WFC) with their levels of pay satisfaction. Results based on two waves of data indicate that pay satisfaction has a negative relationship with WFC after controlling for actual pay and other work‐related and family‐related variables. Analysis of pay satisfaction dimensions reveals that satisfaction with benefits and pay structure are negatively related to WFC, whereas satisfaction with pay level and pay raise are not. Number of dependents and level of education moderate the relationship between pay satisfaction and WFC; specifically, having more dependents and higher education attenuates the relationship between pay satisfaction and WFC. Copyright © 2012 John Wiley & Sons, Ltd.